2013
DOI: 10.1371/journal.pone.0064243
|View full text |Cite
|
Sign up to set email alerts
|

Rat Model for Dominant Dystrophic Epidermolysis Bullosa: Glycine Substitution Reduces Collagen VII Stability and Shows Gene-Dosage Effect

Abstract: Dystrophic epidermolysis bullosa, a severely disabling hereditary skin fragility disorder, is caused by mutations in the gene coding for collagen VII, a specialized adhesion component of the dermal-epidermal junction zone. Both recessive and dominant forms are known; the latter account for about 40% of cases. Patients with dominant dystrophic epidermolysis bullosa exhibit a spectrum of symptoms ranging from mild localized to generalized skin manifestations. Individuals with the same mutation can display substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Seven of 14 pups were affected, making determination of inheritance pattern difficult, but it was unlikely to have been recessive; no attempt was made to reproduce this disease. There is also a report of a dominantly inherited, generalized form of DEB in rats . Although the histological and ultrastructural findings were similar to those observed in the present study, the severity, distribution and inheritance pattern differ.…”
Section: Discussionsupporting
confidence: 88%
“…Seven of 14 pups were affected, making determination of inheritance pattern difficult, but it was unlikely to have been recessive; no attempt was made to reproduce this disease. There is also a report of a dominantly inherited, generalized form of DEB in rats . Although the histological and ultrastructural findings were similar to those observed in the present study, the severity, distribution and inheritance pattern differ.…”
Section: Discussionsupporting
confidence: 88%
“…Homozygosity for autosomal dominant traits is relatively rare in human genetics, and its phenotypic expression is frequently much more severe than that of the heterozygous state . Recently, a rat model for dominant dystrophic epidermolysis bullosa showed that homozygous carriers of the mutation are more severely affected than heterozygous ones, demonstrating for the first time a gene‐dosage effect of mutated alleles in this disease . While this has not yet been demonstrated in animal model, we hypothesize that mutation in AAGAB gene at homozygous state could be associated with a higher disease severity that probably leads to non‐viable phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…The analysis of whole-genome re-sequencing data of 1686 cattle revealed that a nonsense mutation (rs876174537) in the COL7A1 gene segregates with EB. Sequence variants in COL7A1 cause epidermolysis bullosa in various species[19,31,32,33,34]. Interestingly, Menoud et al[19] detected the rs876174537 T-allele in three calves with dystrophic EB from the Rotes Höhenvieh cattle breed.…”
mentioning
confidence: 99%